Ekspansi Karir Desainer Grafis Menjadi Desainer Grafik Bergerak sebagai Ruang Besar Dalam Kreatifitas - Yaniadi, Arif (Bina Nusantara University, 2011)
Due to the development of technology in film and video in a decade, there are many opportunities for a graphic designer for more experiments in the moving images. This development brings convenience for both video technology and data transfer or video result, which allows a graphic designer not only saw one static design in print media, but make it more active and dynamic. For instance, if a logo created in motion version, this will enrich and convey the meaning behind the logo, although it appears briefly in 5 seconds duration. A graphic design does not have to be a static or passive; it can float, jump, fly, dance and also change shape into different shapes. After defining the visual elements in motion, it can be achieved stunning results. Some made by techniques which are difficult, and mostly we ask how this could be done.